Tolerance of rice cultivars to aluminum - Ferreira, Reinaldo de Paula; Salgado, Luis Tarcísio; Jorge, Haroldo Duarte (Pesquisa Agropecuaria Brasileira, 2014)
A field experiment was conducted, in a Yellow Red Latosol with high aluminum saturation, with the objective to select rice (Oryza sativa L.) cultivars concerning to aluminum tolerance. The experimental design utilized was randomized blocks, with split-plots, with three replications. Two levels of aluminum saturation (77% and 18%) were applied in the whole-plots, and 30 rice cultivars in the sub-plots. Based on mean grain production under high aluminum level and its Alt parameter, which estimates the response to lime, the cultivars were classified into four groups: tolerants and nonresponsives (TNR); tolerants and responsives (TR); sensitives and responsives (SA) and sensitives and nonresponsives (SNR). The cultivars of the groups TNR and TR were selected for presenting tolerance to aluminum toxicity.